Descriptive skull morphology of Subulo gouazoubira and Mazama nana (Artiodactyla, Cervidae) - Silva, Gabriela Mariano da; Stipp, Amabile Cristina Maroneze; Oliveira, Larissa Rossato [UNESP]; Heupa, Thalita Caroline; Souza, Rodrigo Antonio Martins de (Univ Federal Santa Maria, 2025)
Osteology plays an indispensable role in understanding the normal patterns of different species, serving as the foundation for zoological understanding. Mazama nana is well-known in Brazil; however, basic morphological descriptions of the species are scarce, while Subulo gouazoubira, currently revalidated as Mazama gouazoubira, is also prevalent in Brazil and has recently been the subject of various phylogenetic studies. In this respect, in the present study, 19 cervid heads (16 Subulo gouazoubira and three Mazama nana) were osteologically prepared. Next, computed tomographies (CTs) were performed to enhance the assessment of bone accidents, as well as internal structures and foramina through three-dimensional (3D) reconstruction techniques due to the difficult visibility in intact specimens. A comparison was then made between the reconstructions, digital photographs, and CT cross-sections of the skull, which enabled the visualization of anatomical peculiarities and exclusivities, such as nasolacrimal-maxillary fenestra, paranasal sinuses, and thin bone architecture, as well as the unique of cranial bones, compared to other species that exhibit a unique and genuine phenotype.
Keywords: Cervidae; description; osteology; skull; tomography